Metabolomic insights into flavour precursor dynamics during fermentation of cacao beans cultivated in diverse climatic production zones in Colombia - Llano, Sandra; Zorro González, Andrés; Santander, Margareth; Vaillant, Fabrice; Boulanger, Renaud; Ocampo Serna, Diana Marcela; Escobar, Sebastián (Elsevier Ltd, 2025)
The market for flavour superior quality cacao provides significant economic and non-economic benefits to farmers. Flavor precursor metabolites, formed during various post-harvest stages, are crucial for developing superior sensory attributes. However, identifying these metabolites and understanding how climate variations and post-harvest practices influence them remains a challenge. This study investigates how the fermentation methodology applied and climate conditions in different zones of the cacao beans producing region of Arauca – Colombia, influence the metabolomic profile of cacao beans and their flavour precursor metabolites. Untargeted metabolomic analysis was performed by UHPLC-ESI-Orbitrap-MS on cacao beans fermented for 0, 24, 48, 72, 96, and 120 h from 9 production zones. The PLS-DA model highlighted that the metabolomics fingerprint changes through fermentation time. Among the most discriminant metabolites, 18 oligopeptides, sucrose, glucose, fructose, flavanols, and acids were tentatively identified. The chemometric analysis showed that fermentation time has a significant impact on the metabolomic profile of cacao beans, while agroclimatic conditions had a minor influence. Metabolomic analyses defined 96 h as the optimal fermentation time to maximize the amount of aroma precursors. Metabolomic analyses identified 96 h as the optimal fermentation time to maximize the amount of aroma precursors across all 9 cacao production zones evaluated. This study underscores the central role of fermentation in shaping flavor precursors, and contributes to the development of new approaches for cacao processing based on the tracking of biochemical and functional compounds (quality biomarkers).